Sea level and climatic influences on the occupation of Qatar and the Gulf during the Holocene period - Macumber, Phillip G. (Proceedings of the Seminar for Arabian Studies, 2018)
Major environmental changes brought about by climatic and sea-level fluctuations dictated the nature, extent, and distribution of Qatar's population in the Holocene period. During the Hydrological Optimum from c. 7700-6000 years BP (revised from Macumber 2011: 8), the climate was wetter with 2-3 m higher sea levels. A Qatar-wide fresh groundwater lens formed with copious coastal spring outflow, enabling widespread Neolithic occupation including large areas in the south which are not habitable today. This was followed by mid- to late-Holocene phases of aridity to hyper-aridity and severe aquifer salinity, resulting in the abandonment of the south and occupation where present, restricted to northern areas underlain by remnants of the former groundwater lens. Vita-Finzi (1978: 24) and Drechsler et al. (2016: 103) note a dearth of occupation from Neolithic to early Islamic times, while more generally Uerpmann (2003) observes a 'Dark Millennium' across eastern Arabia after 5800 years BP. The processes responsible for the changing distribution of populations include an early to mid-Holocene westwards shift in the Inter Tropical Convergence Zone (ITCZ) and monsoonal incursion into Qatar; a 2000 year-long mid-Holocene Saline Event stemming from severe seawater intrusion into the coastal aquifer system from the then high-level coastal shoreline; and mid- to late Holocene aridity including a c.3000 year-long hyper-arid phase. The marine regression from 4000 years BP led to the flushing of intruded seawater from the aquifer onto the newly emerging coastal plain instigating the development of coastal sabkha, which thereafter captured the coastward flowing groundwater in a near-coast hyper-saline zone. The profound environmental changes documented in Qatar have broader implications for occupation elsewhere along the Gulf, being strongest wherever flat hinterlands occur.